2021
DOI: 10.1186/s13063-021-05396-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial to assess the effectiveness of pre- and post-surgical pelvic floor physiotherapy for bowel symptoms, pelvic floor function, and quality of life of patients with rectal cancer: CARRET protocol

Abstract: Background There is scarcity of trials about preventative strategies for low anterior resection syndrome (LARS) in rectal cancer patients. The aim of this study is to evaluate the effectiveness of a pre- and post-surgical pelvic floor rehabilitation program on the bowel symptoms, pelvic floor function, and quality of life of rectal cancer patients. Methods A randomized controlled trial with parallel groups (pelvic floor rehabilitation versus contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Burch’s research ( 2021 ) showed that the quality of life of patients after rectal cancer surgery is not high. Pelvic floor muscle function exercise ( Sacomori et al, 2021 ), sacral nerve stimulation ( Kuo et al, 2015 ), biofeedback training ( Liu et al, 2019 ). Which can effectively alleviate patients’ bowel symptoms and improve their quality of life, but there are no high-quality studies that show the most appropriate treatment method.…”
Section: Discussionmentioning
confidence: 99%
“…Burch’s research ( 2021 ) showed that the quality of life of patients after rectal cancer surgery is not high. Pelvic floor muscle function exercise ( Sacomori et al, 2021 ), sacral nerve stimulation ( Kuo et al, 2015 ), biofeedback training ( Liu et al, 2019 ). Which can effectively alleviate patients’ bowel symptoms and improve their quality of life, but there are no high-quality studies that show the most appropriate treatment method.…”
Section: Discussionmentioning
confidence: 99%
“…The studies commenced interventions at different time points, as summarized in Table 4. One study was pre-habilitative [16], with education and regimes commencing preoperatively. One study was early rehabilitative [15], between resection and stoma reversal, and three studies were rehabilitative [14,17,18] commencing PFP after LAR or stoma reversal.…”
Section: Interventionmentioning
confidence: 99%
“…One study investigated PFP only [14], three studies included BF and rectal balloon training [16][17][18], while Cho et al [15] compared the efficacy between combined PFP and BF, and PFP alone.…”
Section: Interventionmentioning
confidence: 99%
“…Preventative PFR has been used extensively outside of colorectal medicine. Since project conclusion, a current literature review now reveals one randomized clinical trial pilot study looking at PFR as a preventative therapy for LARS [29].…”
Section: Summary and Interpretationmentioning
confidence: 99%